Metro 2033 / Dmitry Glukhovsky. - Glukhovskiĭ, Dmitriĭ (Gollancz, 2011)
2033. The world has been reduced to rubble. Humanity is nearly extinct. A few thousand live on in the Moscow Metro, not knowing if they are the only survivors. It is a world without a tomorrow, with no room for dreams, plans, hopes. Feelings have given way to instinct - the most important of which is survival. Survival at any price.